2014
DOI: 10.1155/2014/542809
|View full text |Cite
|
Sign up to set email alerts
|

On the Generalized Mass Transport Equation to the Concept of Variable Fractional Derivative

Abstract: The hydrodynamic dispersion equation was generalized using the concept of variational order derivative. The modified equation was numerically solved via the Crank-Nicholson scheme. The stability and convergence of the scheme in this case were presented. The numerical simulations showed that, the modified equation is more reliable in predicting the movement of pollution in the deformable aquifers, than the constant fractional and integer derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Recent theoretical and experimental studies have shown that transport processes in complex media are often characterized by either hybrid or anomalous mechanisms. Further, the nature of the transport processes transitions across very different underlying physical phenomena such as transitions from sub-diffusive flow to diffusive flow, and from diffusive flow to superdiffusive flow [34,127,128,[160][161][162]. These complex transport processes have been observed experimentally in various fields, including fluid flow through porous media [5,[134][135][136]163,164], reaction-diffusion interactions between chemical substances leading to pattern formations in nature [165][166][167], diffusion of ions in human neurons [168], analysis of financial data [169], advection-diffusion of groundwater [134][135][136] and elastography [7].…”
Section: Application Of Vo-fc To the Modelling Of Transport Processesmentioning
confidence: 99%
“…Recent theoretical and experimental studies have shown that transport processes in complex media are often characterized by either hybrid or anomalous mechanisms. Further, the nature of the transport processes transitions across very different underlying physical phenomena such as transitions from sub-diffusive flow to diffusive flow, and from diffusive flow to superdiffusive flow [34,127,128,[160][161][162]. These complex transport processes have been observed experimentally in various fields, including fluid flow through porous media [5,[134][135][136]163,164], reaction-diffusion interactions between chemical substances leading to pattern formations in nature [165][166][167], diffusion of ions in human neurons [168], analysis of financial data [169], advection-diffusion of groundwater [134][135][136] and elastography [7].…”
Section: Application Of Vo-fc To the Modelling Of Transport Processesmentioning
confidence: 99%
“…This approach is very recent, and many work has to be done for a complete study of the subject (see, e.g., (Atangana and Kilicman, 2014;Coimbra, Soon and Kobayashi, 2005;Sheng et al, 2011;Valério et al, 2009) Expansion formulas for fractional derivatives…”
Section: Fractional Variational Problems Of Variable-ordermentioning
confidence: 99%
“…Then we may seek what is the best function α(·) such that the variable order fractional differential equation D α(·) y(t) = f (t, y(t)) better describes the model. This approach is very recent, and many work has to be done for a complete study of the subject (see, e.g., [2,3,13,14,17]).…”
Section: Introductionmentioning
confidence: 99%